2021
DOI: 10.3389/fcell.2021.687117
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of MicroRNAs in Tendon Healing and Regeneration

Abstract: Tendons connect the muscle abdomen of skeletal muscles to the bone, which transmits the force generated by the muscle abdomen contraction and pulls the bone into motion. Tendon injury is a common clinical condition occurring in certain populations, such as repeated tendon strains in athletes. And it can lead to substantial pain and loss of motor function, in severe cases, significant disability. Tendon healing and regeneration have attracted growing interests. Some treatments including growth factors, stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 97 publications
(114 reference statements)
0
10
0
Order By: Relevance
“…9 In relation to tendon repair and regeneration, miRNAs have been shown to be involved in regulating biological processes, such as cellular proliferation, inflammation, and homeostasis. 7 Therefore, we used small RNA sequencing to identify the miRNA profiling of 2 EV subtypes isolated from ASCs, and our results revealed a difference between the ASC-Ecto and ASC-Exo miRNA expression profiles, which could further discriminate the ectosomes from exosomes, as well as provide evidence for explaining their different role in the treatment of tendinopathy. This is consistent with a previous study that found that different EV populations vary in their miRNA composition.…”
Section: Discussionmentioning
confidence: 88%
“…9 In relation to tendon repair and regeneration, miRNAs have been shown to be involved in regulating biological processes, such as cellular proliferation, inflammation, and homeostasis. 7 Therefore, we used small RNA sequencing to identify the miRNA profiling of 2 EV subtypes isolated from ASCs, and our results revealed a difference between the ASC-Ecto and ASC-Exo miRNA expression profiles, which could further discriminate the ectosomes from exosomes, as well as provide evidence for explaining their different role in the treatment of tendinopathy. This is consistent with a previous study that found that different EV populations vary in their miRNA composition.…”
Section: Discussionmentioning
confidence: 88%
“…To investigate the mechanisms underlying miR-21-5p-induced fibrogenesis in the tendon-bone tunnel surface, we selected SMAD7 as a candidate gene. Studies have shown that the TGF-β/SMAD signaling pathway contributes to the tendon repair and adhesions [ [87] , [88] , [89] ]. TGF-β is a multi-functional mediator that regulates proliferation, differentiation, apoptosis, adhesion, and migration in various cells, and TGF-β1 is considered a crucial mediator of tissue fibrosis [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…The search line included the following terms: (micro RNA OR miR OR miRNA OR microRNA OR circRNA OR circulating RNA OR ciRNA) AND (tendon OR tendinopathy OR tendinosis OR tendinitis OR tendosynovitis OR tenocytes OR ruptures OR connective tissue) AND (physiology OR pathology OR pathophysiology OR maladaptation OR load OR intervention OR adaptation OR baseline OR timepoint OR pre-post OR comparison). Additionally, the reference list of two previous systematic [31,32] and five previous narrative reviews [29,30,[35][36][37] within the particular research field were screened for further suitable studies. After duplicates were removed, the abstracts and full texts of the remaining studies were checked for their fit by taking the eligibility criteria into account.…”
Section: Literature Search Strategy and Study Selectionmentioning
confidence: 99%